TINJAUAN PROSEDUR PENCAIRAN DANA LANGSUNG GAJI PEGAWAI PADA DIREKTORAT JENDERAL PENGEMBANGAN EKONOMI DAN INVESTASI DESA, DAERAH TERTINGGAL, DAN TRANSMIGRASI - Risda (2023)
The Directorate General of Economic Development and Investment for Villages, Disadvantaged Areas, and Transmigration is a Ministry that has the task of organizing the formulation and implementation of policies in the field of economic development and investment in villages, disadvantaged areas, and transmigration. With this final project, the author aims to deepen and study the procedures for direct disbursement of employee salaries at the Directorate General of PEI. The disbursement of direct employee salary funds starts with the staffing department making a salary list, and is delivered to the salary treasurer. The next stage is the salary treasurer inputting the Salary ADK (Computer Data Archive) and reconciling the Salary ADK, and the documents are submitted to the Commitment Making Officer (PPK) and the PPK issues the SPP-LS. The next stage is the SPM section issues the SPM-LS Salary, and the Head of the General Section verifies, and initials. Then, the documents are submitted to the salary treasurer, and the salary treasurer submits a Tax Payment Slip Article 21. All files are submitted to KPPN to issue SP2D-LS. Then, the Bank disburses the funds to the party applying for the disbursement.